Incorporation of Social and Moral Values through Secondary School Textbooks of Urdu: A Content Analysis - Junaid Ahamad, Malik; Khan , Muhammad Ilyas (The Lighthouse Journal of Social Sciences, 2024)
This research work was focused to explore incorporation of social and moral values through secondary school textbooks of Urdu. The study examined inclusion of social and moral values, aiming to understand the presence, benefits and gaps in these values. The study population included secondary-level textbooks of Urdu and the secondary school teachers from Mansehra district. Using purposive sampling technique, the lessons about social and moral values from the textbooks of Urdu and twelve secondary school teachers were taken as sample of the study. Qualitative content analysis method was used for analyzing text data of textbooks and transcribed interviews of secondary school teachers. Findings of the study highlighted that social values like; service of humanity, unity, patriotism and dignity of labor and moral values like good manners, virtue and sacrifice were included in the textbooks. Secondary school teachers argued that social values are shared principles, beliefs and habits those are the foundation stone of a society whereas moral values are standard of goodness that can shape honorable and righteous human personality. This study recommended incorporating additional moral values; honest and fair dealings, tolerance and patience in behavior, submission, trust, honor, chastity and goodness of behavior. Some more social values; responsibility in performing duties, charity, social justice, rights of deprived people like women and children, affection and respect for family and labor rights, may be included in the textbooks. These values can be used for making students ethically reformed and socially responsible citizens of their country.